Prevalence of disrespectful maternity care in hospitals affiliated with TUMS and its associated factors - Elham Shakibazadeh; Fahimeh Taherkhani; Mir Saeid Yekaninejad; Davod Shojaeizadeh; Maryam Tajvar (Tehran University of Medical Sciences, 2021)
Background & Aim: In recent years, women's experience of disrespect and misconduct during childbirth has been raised as a significant problem around the world. This study aimed to determine the prevalence of disrespectful maternity care and its associated factors. Methods & Materials: This is a cross-sectional study conducted in 2019 on 357 mothers who gave birth at hospitals affiliated to TUMS. The data collection tool included socio-demographic characteristics form, and the disrespectful maternity care questionnaire, measuring various domains of abuse. The questionnaire was completed by interviewing mothers. Data was analyzed using descriptive tests, Chi-square test and multivariate logistic regression through the SPSS software version 24. Results: All participants reported at least one form of disrespect, of which "not allowing for mobility, fluid and companion" was the most prevalent (99.7%) and "stigma and discrimination" was the least prevalent (4.5%). Statistical analysis showed a significant relationship between older age, ethnic minority, primiparity, higher socioeconomic status, delivery time (night, day) and a history of illness with more experience of different forms of disrespect. Conclusion: This study confirmed a relatively high prevalence of disrespectful maternity care in hospitals based on international standards, which requires serious and prompt attention of top-level managers to take action to eliminate or limit this type of behavior.